2015
DOI: 10.15244/pjoes/26203
|View full text |Cite
|
Sign up to set email alerts
|

Surface Water Quality in Relation to Land Cover in Agricultural Catchments (Liswarta River Basin Case Study)

Abstract: Agricultural activity results in ground and surface water pollution from nitrogen and phosphorus compounds, which results from the excessive use of fertilizers containing these ingredients [1,2]. High concentrations of nitrogen compounds pose a threat to animal and human health and, in the case of surface waters (lakes, seas, and rivers), these pollutants can lead to eutrophication, which disturbs the ecological balance of the aquatic environment [3][4][5][6].Clean water is vital to human life and the proper f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…After the pre-incubation period, an ammonium nitrate solution (with the same concentration as used in the batch tests) was added to each bottle at a rate of 1:5 (soil-to-solution) and stored in the dark under the same conditions as those used in the pre-incubation process. At each desired incubation time (1,4,7,10,15,20, and 30 days) the treatment solutions were removed from the bottles for laboratory testing to track temporal changes and variations in the selected parameters.…”
Section: Batch Incubationmentioning
confidence: 99%
See 1 more Smart Citation
“…After the pre-incubation period, an ammonium nitrate solution (with the same concentration as used in the batch tests) was added to each bottle at a rate of 1:5 (soil-to-solution) and stored in the dark under the same conditions as those used in the pre-incubation process. At each desired incubation time (1,4,7,10,15,20, and 30 days) the treatment solutions were removed from the bottles for laboratory testing to track temporal changes and variations in the selected parameters.…”
Section: Batch Incubationmentioning
confidence: 99%
“…According to Camargo and Alonso [5], Moradzadeh et al [6], and Matysik et al [7], the concentrations of these ions in surface and groundwater increase worldwide, affecting aquatic organisms and ecosystem quality. Therefore, following the ratification of the Nitrates Directive [8], the EU member states have committed themselves to regularly assessing groundwater and surface water pollution by nitrogen compounds from agricultural sources.…”
mentioning
confidence: 99%
“…Many studies have indicated that human activities have the potential to change water environments [1][2][3][4][5][6][7][8]. Eutrophication is the most obvious environmental water problem in recent years worldwide [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, agricultural activities are a source of elevated concentration of contaminants [6][7][8][9]. The use of chemical fertilizers has increased from 14 million tons in 1954 to a predicted 200 million tons in 2018 [10].…”
mentioning
confidence: 99%